Antibacterial Screening On Foeniculum Vulgare Mill.R. - R. MANONMANI; V. MOHIDEEN ABDUL KHADIR (International Journal of Pharma and Bio Sciences, 2011)
Ethanol, methanol and aqueous extracts of Foeniculum vulgare Mill. seeds were investigated for in vitro antibacterial screening by Agar well and Disc diffusion method against Escherichia coli, Klebsiella pneumoniae, Proteus vulgaris, Enterobacter aerogeus, Salmonella typhi, Bacillus cereus and Staphylococcus aureus. In Both agarwell and disc diffusion methods, the highest inhibition zone was found in aqueous extracts. It showed greater activity against the maximum tested bacteria followed by ethanol and methanol extract. The preliminary results of this study indicate that the aqueous seed extracts have potentials for antibacterial activity.